A DIVULGAÇÃO CIENTÍFICA NO CONTEXTO ORGANIZACIONAL PARA DEMOCRATIZAÇÃO DO SABER E LEGITIMAÇÃO DAS UNIDADES DE PESQUISA - ANDRADE, GIULIANA CAPISTRANO CUNHA MENDES DE (2017)
The beginning of the 21st century is marked by the propagation of actions related to the scientific dissemination. Still, the science-producing centers of Brazil do have no visibility compatible with the interest of contemporary society and only a small part of the Brazilian population has access to the science produced in the country. This study aims to evidence the importance of scientific dissemination in the organizational context for the democratization of scientific knowledge and as an important resource for legitimizing research units in relation to the lay public and the media. The investigation was developed through a bibliographical research and empirical study through a single case study of the Laboratório Nacional de Astrofísica (LNA) research unit. The data were obtained from the consultation of archives and analysis of documents, in-depth interviews conducted with managers and researchers of the LNA, questionnaires to journalists and direct and participant observation of the disclosure actions carried out by the institution. The data were analyzed in agreement with the theories about concepts and practices of scientific dissemination, identity, image and organizational reputation and communication policy that constituted the initial and final chapters of this study. It is concluded, among other aspects, that scientific dissemination is carried out in the institution studied, but that its role is not seen as a priority, since the target audience is not considered strategic. The actions of scientific dissemination carried out by the research unit are conducted without the guidance of a dissemination plan and therefore present problems that compromise the institutional visibility.